2020
DOI: 10.1186/s12916-020-01600-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of body mass index across the adult life span on the risk of dementia: a cohort study with a genetic approach

Abstract: Background: While a high body mass index (BMI) in midlife is associated with higher risk of dementia, high BMI in late-life may be associated with lower risk. This study combined genetic designs with longitudinal data to achieve a better understanding of this paradox. Methods: We used longitudinal data from 22,156 individuals in the Swedish Twin Registry (STR) and 25,698 from the Health and Retirement Study (HRS). The STR sample had information about BMI from early adulthood through late-life, and the HRS samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
2
36
0
1
Order By: Relevance
“…Our findings indicated small but significant genetic influences assessed by the PGS BMI , such that the effects of BMI on cognitive abilities were most prominent among those with genetic predisposition to a low BMI. Similarly, we have previously shown that a higher BMI in midlife predicts dementia only among those with a genetic predisposition to a low BMI 19 . This may indicate that a higher BMI due to environmental factors (such as a sedentary lifestyle and diet) has different consequences than a higher BMI due to genetic predisposition.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our findings indicated small but significant genetic influences assessed by the PGS BMI , such that the effects of BMI on cognitive abilities were most prominent among those with genetic predisposition to a low BMI. Similarly, we have previously shown that a higher BMI in midlife predicts dementia only among those with a genetic predisposition to a low BMI 19 . This may indicate that a higher BMI due to environmental factors (such as a sedentary lifestyle and diet) has different consequences than a higher BMI due to genetic predisposition.…”
Section: Discussionsupporting
confidence: 59%
“…Use of self-reported height and weight to calculate BMI, specifically in longitudinal aging studies, has been validated against in-person measures previously 18 . The BMI data were cleaned prior to analyses, the process described in detail elsewhere 19 , removing outliers (1515 individuals, or 4% of the total HRS sample) including those that had values considered out-of-range (e.g., height below 1.47 or above 2.10 m, BMI below 15 or above 55) and unreasonably large changes between waves. BMI at baseline was categorized into normal weight (18.5–24.9), overweight (25–29.9), and obesity (30 and above).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings indicated small but significant genetic influences assessed by the PGSBMI, such that the effects of BMI on cognitive abilities were most prominent among those with genetic predisposition to a low BMI. Similarly, we have previously shown that a higher BMI in midlife predicts dementia only among those with a genetic predisposition to a low BMI [19]. This may indicate that a higher BMI due to environmental factors (such as a sedentary lifestyle and diet) has different consequences than a higher BMI due to genetic predisposition.…”
Section: Discussionmentioning
confidence: 82%
“…Use of self-reported height and weight to calculate BMI, specifically in longitudinal aging studies, has been validated against in-person measures previously [18]. The BMI data were cleaned prior to analyses, the process described in detail elsewhere [19], removing outliers (1,515 individuals, or 4% of the total HRS sample) including those that had values considered out-of-range (e.g., height below 1.47 or above 2.10 meters, BMI below 15 or above 55) and unreasonably large changes between waves. BMI at baseline was categorized into normal weight (18.5-24.9), overweight (25-29.9), and obesity (30 and above).…”
Section: Bmi Measurementsmentioning
confidence: 99%
“…Height and weight were measured by trained research nurses as part of the health examinations during each in-person testing occasion. The measures have been thoroughly examined for outliers, both quantitatively and visually by plotting individual trajectories over time, as described in detail previously [12]. BMI was calculated as kilograms divided by height (in meters) squared.…”
Section: Bmi Measurementsmentioning
confidence: 99%